Music-based interventions in rehabilitation of children and adolescents with chronic diseases: Sharing an experience from a Brazilian public hospital - Sampaio, Anna-Dulce Sales Carneiro (Frontiers in Rehabilitation Sciences, 2023)
Music-based interventions (MBI) in therapeutic routine have been observed as an effective tool for adjuvant therapy for patients with chronic diseases and for those with various types of disabilities. Music can serve as a pedagogical and therapeutic strategy for development of psychomotor skills in children and adolescents with long-lasting illnesses, and also as a secular way of promoting comfort and spiritual health for patients and families during difficult times; it can also be used to alleviate suffering during diagnostic and therapeutic procedures throughout the long recovery and/or rehabilitation processes. In this article, a musician and art therapist describes some simple MBI used daily in a tertiary children's hospital in Sao Paulo, where patients with chronic diseases and from lower socioeconomic background represent most of outpatients and inpatients. Some MBI developed or adapted by the author are described in detail, some of them using only the voice and others utilizing simple musical instruments, usually percussion ones, by the patients themselves. There are also reports describing MBI in special situations, such as long-lasting isolation of immunosuppressed patients (for bone marrow transplantation, for example), regular day-hospital visits for hemodialysis and religious songs for families of end-of-life or critically ill patients. In conclusion, MBI can be beneficial for improving patient experience in hospital settings, particularly for those with long-lasting or repeated stays, and can be performed in a simple and playful way, with contribution of other health professionals with some background in music, since music therapy specialists are still scarce in many countries.